The Strategy for Strengthening Kampung Siaga Bencana through a Participatory Information System in Ujungberung Bandung - Fajar Khoerul; Aribowo Aribowo; Milly Mildawati (Indonesian Journal of Social Work, 2026)
Kampung Siaga Bencana (KSB) is a community-based disaster risk reduction initiative aimed at strengthening local community capacity in disaster management. However, disaster information management at the grassroots level remains constrained by top-down and technocentric reporting systems, weak coordination among volunteers, fragmented data management, and limited community participation. This study aims to formulate the strategy for strengthening KSB through a Participatory Disaster Information System (Sistem Informasi Partisipatif/SIP) in Ujungberung, Bandung. The study employed a Participatory Action Research (PAR) approach by involving KSB volunteers as co-researchers, facilitated through the Technology of Participation (ToP) method. Data were collected through in-depth interviews, Focus Group Discussions (FGDs), observation, and documentation studies, and analyzed using the Miles and Huberman interactive model. The findings reveal five major community needs in developing the system: (1) integrated disaster data management across pre-disaster, emergency response, and post-disaster phases; (2) smartphone-based rapid reporting with real-time visual documentation; (3) volunteer competency mapping for tactical mobilization; (4) user-friendly application interfaces; and (5) managerial clarity regarding system operators within the KSB structure. The development of SIP transformed the previous system (SIGERCEP) into a participatory digital platform that improved information management and emergency coordination while strengthening participation, sense of ownership, empowerment, and community resilience. The study also found that community strengthening is influenced not only by internal community capacities, but also by local leadership support, inter-agency communication, coordination among stakeholders, and linkages with government and disaster management institutions. The novelty of this study lies in integrating social work approaches, strengths perspective, community empowerment, and digital transformation into a participatory disaster information system model for community-based disaster risk reduction. Keywords: Kampung Siaga Bencana (KSB); Participatory Information System; Community Empowerment; Strengths Perspective; Community Resilience.